2017
DOI: 10.1089/aid.2016.0113
|View full text |Cite
|
Sign up to set email alerts
|

Association of T Cell and Macrophage Activation with Arterial Vascular Health in HIV

Abstract: HIV-infected individuals are at increased risk of cardiovascular disease (CVD), but the arterial vascular functions affected by persistent innate and cellular immune activation are not well described. We assessed the relationship between immunologic and vascular parameters in 70 HIV-infected adults on efavirenz, tenofovir, and emtricitabine with more than 2 years of virologic suppression and no history of CVD. We measured brachial artery flowmediated dilation (FMD) using ultrasound and circulating intercellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…Conversely, other inflammatory biomarkers, including IL-8 and RANTES were directly correlated with improved FMD in this group. These results contrast with those of Grome et al [ 51 ] who found that activated CD8+ cells, but not sTNFRII, were associated with FMD in 70 HIV-infected patients who were similarly treated with FTC/TDF/EFV. We also found that RANTES was significantly correlated with FMD, but not FMD/RHVTI in the HIV- group.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, other inflammatory biomarkers, including IL-8 and RANTES were directly correlated with improved FMD in this group. These results contrast with those of Grome et al [ 51 ] who found that activated CD8+ cells, but not sTNFRII, were associated with FMD in 70 HIV-infected patients who were similarly treated with FTC/TDF/EFV. We also found that RANTES was significantly correlated with FMD, but not FMD/RHVTI in the HIV- group.…”
Section: Discussioncontrasting
confidence: 99%
“…It is postulated that the increased prevalence of cardiovascular diseases in HIV patients is due to activation of the immune system. Specifically, macrophages and monocytes activation, which play a significant role in atherogenesis, in combination with deregulation of CD8+ T-cells, are associated with higher values of carotid intimal media thickness and arterial stiffness 41 Likewise, HIV and periodontitis could interact and promote development of ageassociated diseases 23,42 . We could not confirm that diabetes and cardiovascular diseases were significant risk factors for periodontitis in our HIV-infected patients, however.…”
Section: Discussionmentioning
confidence: 99%
“…Even HIV elite controllers have abnormally high T cell activation levels, which may contribute to progressive CD4 + T cell loss, even without measurable viremia (52). Chronic immune activation might contribute to the initiation of endothelial activation and subsequent atherogenesis (53), and these markers of T-cell activation are correlated with atherosclerosis in several studies (5056).…”
Section: Underlying Cellular Mechanismsmentioning
confidence: 99%